Get the answers you need at Westonci.ca, where our expert community is dedicated to providing you with accurate information. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.

Solve using substitution.y = -x - 1y = x + 3Submit

Sagot :

y = -x - 1 (a)

y = x + 3 (b)

Replace the value of y in the first equation (a) by the value of y in the second equation (b).

x+3=-x-1

Solve for x

x+x=-1-3

2x=-4

x=-4/2

x= -2

Replace the value of x in (a) or (b)

y=-x-1

y= -(-2)-1

y= 2-1

y=1